(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
This paper examines the stylistics of the speech of the Russian writer Alexander Solzhenitsyn at Harvard University in 1978. The aim of the work is to use certain methods, such as analysis and synthesis, proof and refutation, to draw a conclusion about how and to what extent a well-constructed word, including logos, ethos and pathos, can impress the audience. Revealing the structure of the parts of the speech, taking into account its meaning and logical connections, we can conclude that Solzhenitsyn’s speech was noticed, thanks to the unifying effect of the triad (speech, speaker, audience).